OPTIMALISASI MANAJEMEN RANTAI PASOK DAN KEUNGGULAN BERSAING UNTUK MENINGKATKAN KINERJA PERUSAHAAN PADA AUTO2000 YASMIN BOGOR - Riva Aryani Putri; Endang Silaningsih; Yulianingsih Yulianingsih (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This study aims to examine the optimization of supply chain management and competitive advantage on company performance. The research object is Auto2000 Yasmin Bogor, an official Toyota dealer that implements a one-stop service concept covering sales, service, and spare parts. The research sample consists of 75 employees selected using a non-probability sampling approach with a saturated sampling technique. Data were collected through questionnaires, and data analysis was performed using multiple linear regression with the assistance of SPSS version 27.0.1. The results indicate that supply chain management has a positive and significant effect on company performance, and competitive advantage also has a positive and significant effect on company performance. Simultaneously, both variables contribute significantly to improving company performance at Auto2000 Yasmin Bogor. These findings suggest that strengthening supply chain management and enhancing competitive advantage are essential strategies for achieving optimal company performance.